Urgency of Esophageal Foreign Body Removal: Differentiation Between Coins and Button Cell Batteries. (4th May 2021) - Safavi, Arash R.; Brook, Christopher D.; Sakai, Osamu; Setty, Bindu N.; Zumwalt, Ann; Gonzalez, Mauricio; Platt, Michael P.
Abstract : Objective: Coin‐shaped button battery foreign bodies have a similar initial presentation to coin ingestion, but delayed retrieval of a battery from the esophagus can have devastating consequences. Variations in timing of retrieval for children with ingestion of coin foreign bodies have been reported. The study assesses the sensitivity and specificity of conventional and digital radiographs to differentiate button batteries from coin foreign bodies. Study Design: 3B case control study. Study Setting: Tertiary academic medical center. Methods: A radiographic study of the 12 most common commercially available button batteries and 66 coins of varying international origins was performed. Foreign bodies were placed at the cervical esophagus of a cadaver, and anteroposterior (AP) and lateral conventional radiographs of the neck were obtained. Digital AP and lateral radiographs of standalone coins and batteries were also obtained. Images were blindly read by 2 otolaryngologists and 2 radiologists. Statistical analysis was performed to determine accuracy in identifying coins vs batteries. Results: Using conventional radiographs to identify button batteries yielded a sensitivity of 0.88 and a specificity of 0.92 (positive predictive value [PPV] = 0.75, negative predictive value [NPV] = 0.97). Digital radiography yielded an overall sensitivity of 0.98 and specificity of 0.97 (PPV = 0.87, NPV = 0.99). Features of button batteries were only seen on AP conventional radiographs using reverse contrast. Conclusions: Neither conventional nor digital radiographic imaging had perfect accuracy in identifying coins vs batteries. Features of common disc batteries were identified, which may aid in diagnosis. With potential devastating consequences from retained battery in the esophagus, emergent removal of any possible disc battery foreign body should be considered.